Development of Project Based Learning E-Modules in Chemistry Learning Design Course Using Flipbook Builder Application - Wilda Syahri; Fuldiaratman; Firdiawan Ekaputra (Postgraduate, University of Mataram, 2024)
The purpose of this study was to develop a project-based learning e-module in chemical learning design courses using the flipbook builder application. The method used in this research is the Research and Development method to develop project-based learning e-modules in chemical learning design courses using the flipbook builder application. The e-module media development model used in this study, namely the ADDIE model which consists of 5 stages including analysis, design, development, implementation, and evaluation. The subjects used in this study were students of the Chemistry Education Study Program at Jambi University who had taken a chemistry learning design course, namely 15 students in the small scale test and 30 students in the large scale test. Based on the feasibility test assessment of project-based learning e-modules in chemistry learning design courses that have been developed on a small scale, the score is 89.33 with very high criteria, while the large-scale feasibility test scores 91.83 with very high criteria.